2011
DOI: 10.1155/2011/948406
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and the Airway Epithelium

Abstract: The airway epithelium functions as a barrier and front line of host defense in the lung. Apoptosis or programmed cell death can be elicited in the epithelium as a response to viral infection, exposure to allergen or to environmental toxins, or to drugs. While apoptosis can be induced via activation of death receptors on the cell surface or by disruption of mitochondrial polarity, epithelial cells compared to inflammatory cells are more resistant to apoptotic stimuli. This paper focuses on the response of airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 236 publications
(281 reference statements)
2
43
1
Order By: Relevance
“…Consistently, a previous study reported NET‐induced apoptosis of A549 cells . The survival of AECs requires adhesion to basement membranes; consequently, cell detachment is followed by cell death . In the present study, NETs down‐regulated the expression of epithelial TJ proteins, occludin and claudin‐1, which could be a mechanism of NET‐induced AEC detachment followed by cell death.…”
Section: Discussionsupporting
confidence: 91%
“…Consistently, a previous study reported NET‐induced apoptosis of A549 cells . The survival of AECs requires adhesion to basement membranes; consequently, cell detachment is followed by cell death . In the present study, NETs down‐regulated the expression of epithelial TJ proteins, occludin and claudin‐1, which could be a mechanism of NET‐induced AEC detachment followed by cell death.…”
Section: Discussionsupporting
confidence: 91%
“…Exposure to environmental pollutants, allergens and pathogens can induce apoptosis of airway epithelial cells 3,6,4,7 . In fact, clusters of uncleared epithelial cells referred to as ‘Creola bodies’ in the sputum have been seen in patients with asthma for decades 8,9 .…”
mentioning
confidence: 99%
“…; Basinski et al. ), we were unable to elicit apoptosis exclusively through exposure to TNFα and IFNγ, a situation which may reflect differences in cell culture (White ). For example, unlike AECs cultured directly from donors, the commonly used normal human bronchial epithelial (NHBE) cell line can grow on a plastic substratum, and are often examined at subconfluence.…”
Section: Discussionmentioning
confidence: 78%
“…; Makinde et al. ; White ). However, apoptosis of AECs in asthmatics has been observed in the absence of prolonged inflammation, and demonstrate abnormalities for the production of Bcl2 and activation of caspases (Cohen et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation